Improved DOA estimation algorithm for co‐prime linear arrays using root‐MUSIC algorithm. Issue 18 (8th August 2017) - Zhang, Dong; Zhang, Yongshun; Zheng, Guimei; Feng, Cunqian; Tang, Jun
Abstract : The problem of direction of arrival (DOA) estimation with co‐prime linear arrays is researched. An improved DOA estimation algorithm based on root‐multiple signal classification (MUSIC) is proposed. The method can solve the matching error problem in Sun's algorithm. In addition, it can make full use of signal space and noise space to improve the estimation accuracy with low complexity. Experimental results verify the validity of the proposed algorithm.